(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the ideas on the introduction of the institute of "tutoring" in universities, strengthening cooperation between the university and the student, the adaptation of students to the educational environment and socio-pedagogical and psychological support, the special abilities of the leader and the issue of preparation for it, the ways to solve the problem he sets, the nature of the experiment, and its results.